Concentration and Flux of Wind-Blown Snow - Mellor, Malcolm; Fellers, Gregor (1986)
Representative graphical relations are developed for the flux and concentration wind blown snow as functions of wind speed and height above surface. Previously published field data are tabulated to provide 1201 data sets for flux and the same number for mass concentration. Using appropriately transformed variables, multiple regression analysis yields empirical relations for horizontal mass flux as a function of wind speed and height, and for mass concentration as a function of wind speed and height.